1987
DOI: 10.1289/ehp.877679
|View full text |Cite
|
Sign up to set email alerts
|

Placental markers of human exposure to polychlorinated biphenyls and polychlorinated dibenzofurans.

Abstract: Our studies have evaluated biochemical changes in placentae from humans exposed to rice oil contaminated with polychlorinated biphenyls (PCBs) and polychlorinated dibenzofurans (PCDFs) in Taiwan. Placentae were obtained from nonsmoking women 4 to 5 years after the exposure had occurred. The exposed individuals ingested approximately 1 to 3 g PCBs and 5 mg PCDFs, and many exhibited symptoms characteristic of PCB poisoning. This disease was termed "Yu-Cheng" in Chinese. Based on data from experimental animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…Increased placental CYP1A1 activity was reported in women accidentally exposed to high levels of PCBs and PCDFs (6,34). However, the mean placental PCB 153 concentration in these women (Yu-Cheng patients) was about 12-fold greater than that reported here for the Nunavik group (8 ppb vs. 0.64 ± 0.02 ppb when converted to wet weight) (34).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Increased placental CYP1A1 activity was reported in women accidentally exposed to high levels of PCBs and PCDFs (6,34). However, the mean placental PCB 153 concentration in these women (Yu-Cheng patients) was about 12-fold greater than that reported here for the Nunavik group (8 ppb vs. 0.64 ± 0.02 ppb when converted to wet weight) (34).…”
Section: Discussioncontrasting
confidence: 68%
“…Placental CYP1A1 activity (AHH) in Taiwanese women with Yu-Cheng syndrome was also about 10-fold higher than in American women exposed to background levels of organochlorines who smoked during pregnancy (6). In addition, an inverse correlation of ethoxyresorufin-O-deethylase (EROD) and AHH enzyme activities to birth weight was subsequently reported in Yu-Cheng patients (34). These results indicated that accidental exposure to PCBs and PCDFs induced placental CYP1A1 activity and further suggested a relation between placental CYP1A1 activity and adverse developmental effects.…”
mentioning
confidence: 97%
“…Lagueux et al (1999) found that CYP1A1 activity was elevated in the placental tissue of Inuit women living in northern Quebec who are exposed to PCBs and other organochlorine compounds from the consumption of marine mammals. Similarly, Lucier et al (1987) reported that Yu-Cheng women exposed to PCBs and dibenzofurans had higher levels of placental CYP1A1 activity than an unexposed control group, and that such activity was inversely correlated with the birth weight of their offspring.…”
Section: Discussionmentioning
confidence: 94%
“…Placentas from women exposed to contaminated rice oil were analyzed for EGF receptor binding and EGF-stimulated autophosphorylation as well as for CYPlA1 activity; the data are displayed in Table 2 (18,19). These compounds are structurally similar to TCDD and are thought to share the same mechanism of action: binding to the Ah receptor and induction of pleiotropic responses.…”
Section: Human Exposuresmentioning
confidence: 99%